2019
DOI: 10.2144/btn-2019-0045
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies: Will Their Star Continue to Rise?

Abstract: Antibodies are having a huge impact in basic and translational research, but they are also in crisis. Francesca Lake investigates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
(13 reference statements)
0
2
0
Order By: Relevance
“…While this new understanding of human biology should go some way to pushing science forward, antibody-based research has in the past been plagued by problems. Last year we covered antibodies and their reproducibility crisis in detail [9]. At that point, we reported on work from the HPA that had suggested that of 5000 commercial antibodies tested, over 50% were not useful for the proposed application, which is somewhat damning.…”
Section: Revisiting the Reproducibility Questionmentioning
confidence: 99%
“…While this new understanding of human biology should go some way to pushing science forward, antibody-based research has in the past been plagued by problems. Last year we covered antibodies and their reproducibility crisis in detail [9]. At that point, we reported on work from the HPA that had suggested that of 5000 commercial antibodies tested, over 50% were not useful for the proposed application, which is somewhat damning.…”
Section: Revisiting the Reproducibility Questionmentioning
confidence: 99%
“…2 engineering. However, the current administration of antibody therapeutics is restricted to the invasive parenteral route, which presents limitations such as increased risks of systemic toxicity like cytokine release syndrome [13,14].…”
Section: Introductionmentioning
confidence: 99%